Acclimatation of the roe deer (Capreolus capreolus L.) introduced in a supramediterranean habitat and its occupation of space - Maillard, D; Gaudin, J C; Reudet, D; Boutin, J M (REVUE D ECOLOGIE-LA TERRE ET LA VIE, 1999)
In 1988 and 1989, we captured 74 roe deer (Capreolus capreolus) in the Chize National Reserve in France and transferred them to the Monts de Vaucluse. Thirteen individuals were followed by radio-tracking during two years. The study area, a supramediterranean habitat dominated by Quercus humilis and Quercus ilex covered 40,000 ha. The instrumented deer were located daily during the three first months, the longest time required to settle on a home range, and once a week thereafter. These data allowed us to calculate survival rates and size of home ranges. The mean survival rate during the first year after the introduction was 85 %. Except for one adult male and one adult female, all radio-equipped deer established their home range within 3 km of the release site. The time required for definitive establishment on a home range varied from 45 to 85 days after release. The mean area prospected before settling on a home range was greater for adults (n = 5) than for juveniles (n = 6) (2,240 ha vs. 478 ha). Conversely, the mean home range size after the period of prospection was greater for juveniles (n = 6) than for adults (n = 4) (823 ha vs. 342 ha). If capture, transport and release are carried out under good conditions, the roe deer can adapt to the Mediterranean climate and habitat.
APS
Keywords: Chize National Reserve; Quercus humilis; Quercus ilex; roe deer

Cynegetical development of the French Mediterranean ``matorral'' scrublands: Case of wild ungulates - Maillard, D; Melac, O; Gaudin, J C; Vassant, J (GIBIER FANE SAUVAGE - GAME AND WILDLIFE, VOL 15 (SPECIAL NUMBER PTS 2 AND 3) 1998, 1998)
Since the beginning of the seventies, the marorrals (garrigues, maquis, and holly oak, Quercus ilex, copses) are slowly being colonized by roe deer, Capreolus capreolus, white wild boar; Sus scrofa, populations are stongly increasing. This phenomenon is mainly due to a relative low hunting pressure compared to the potential huntable population, to the disappearance of traditional farming practices (rural abandonment) causing the matorrals to extend, to the compensations paid to farmers since 1969, and to an increase in food resources (ageing of holly oak copses). As for red deer, Cervus elaphus, its population is increasing very slowly: The uncontrolled increase in wild boar populations is causing intolerable damages to farmers, especially in high-quality crops (arboriculture, vines, market-garden crops), which have been expanding since the productive lands in the bottom of the valley are being cultivated and agricultural techniques have improved. In the years to come, the ungulates frequenting the garrigue may become a harvestable resource if the two main sympatric species (wild boar and roe deer) which are occupying areas of some 30,000 ha, are wisely managed and the following parameters are taken into account : - amount of food produced in the habitats (annual mast crops); - damage control by controlled hunting in each massif, and damage prevention (protection or dissuation); - appropriate management of ungulate territories and the effective control of their populations based on hunting bag analyses in the middle and at the end of the hunting season. Most of ail it is important that before applying the ``population/environment/damage{''} model in each massif or management unit, clear management objectives be defined in agreement with the farmers.
IUGB XXIIIrd Congress, LYON, FRANCE, SEP 01-06, 1997
Keywords: roe deer; Sus scrofa; Wild boar; wild ungulate

Impact of feeding habits of Corsican red deer (Cervus elaphus corsicanus) on vegetation at Quenza Park in Corsica - Maillard, D; Casanova, J B; Gaillard, J M (MAMMALIA, 1995)
Following the translocation of Corsican red deer (Cervus elaphus corsicanus) in Quenza enclosures in 1985, we tried to assess the impact of red deer on woody mediterranean species. We found that sempervirent species with persistent leaves like Calytcotome villosa, Arbutus unedo, Quercus ilex and Cistus salviaefolius were eaten by deer all the year along. In fact, we identified three different categories of plant species according to the different levels of use by deer. A first groupe includes species highly and quickly consumed by deer like Calycotome villosa, Fraxinus ornus and Lonicera etrusca. These plants can even disappear when deer density becomes very high. A second group was composed of plant species red deer ate but searched for in a lesser extent like Arbutus unedo and Quercus ilex. Consumption of some of them showed a peak during summer (Rosa canina and Rubus sp.). in the last groupe, we pooled species weakly consumed by red deer, like Erica arborea and Cistus salviaefolius.
APS
Keywords: Arbutus unedo; Calytcotome villosa; Cervus elaphus corsicanus; Cistus salviaefolius; comsumption; Mediterranean; Quercus ilex; red deer